2011
DOI: 10.1039/c0cp02551h
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the Belousov-Zhabotinskii reaction derived from EQCM measurements at a gold electrode

Abstract: Electrochemical quartz crystal microbalance experiments were used to study the classical Belousov-Zhabotinskii (BZ) homogeneous oscillating system. This system involves 2 × 10(-3) M Ce(III), 0.28 M malonic acid and 0.063 M bromate as the main initial components in 1 M sulfuric acid solution. The gold-evaporated electrodes on a 10 MHz AT-cut quartz crystal were used for potentiometric and amperometric studies while the changes in crystal frequency provided mass data. Under open-circuit conditions, during the BZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This detection mode allows selective control over the redox species generated electrochemically allowing for new mechanistic insights into the role of an electrode surface state in a BZ process. 44 It also parallels the specific case of inter-microreactors chemical communication as the consumption of ferroin at the tip may approximate the behavior of the efflux of chemicals during inter-reactor communication. Then, the tip−substrate confinement would approximate the shell−core behaviors within communicating microreactors.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…This detection mode allows selective control over the redox species generated electrochemically allowing for new mechanistic insights into the role of an electrode surface state in a BZ process. 44 It also parallels the specific case of inter-microreactors chemical communication as the consumption of ferroin at the tip may approximate the behavior of the efflux of chemicals during inter-reactor communication. Then, the tip−substrate confinement would approximate the shell−core behaviors within communicating microreactors.…”
mentioning
confidence: 75%
“…Unlike potentiometry, amperometry perturbs the system as it enforces the ferroin concentration at the tip. This detection mode allows selective control over the redox species generated electrochemically allowing for new mechanistic insights into the role of an electrode surface state in a BZ process . It also parallels the specific case of inter-microreactors chemical communication as the consumption of ferroin at the tip may approximate the behavior of the efflux of chemicals during inter-reactor communication.…”
mentioning
confidence: 93%
“…However, it has been reported that the adsorption of bromine species and compounds on the QCM electrode dissolved gold. 24 On the other hand, a platinum electrode was sufficient for the oscillation measurement. 23 That is, the difference in the ΔF oscillation due to an electrode metal has not yet been clarified in detail.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been reported that the QCM could be used as a detection tool of the classic BZ oscillation. The classic BZ reaction produces carbon dioxide bubbles as the result of chemical reaction of malonic acid . The bubbles disturb the QCM measurement due to adsorption on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation